Громадсько-політична активність населення європейських країн - Сальнікова, Світлана Анатоліївна; Salnikova, Svitlana А.; Тимчук, Тетяна Олегівна; Tymchuk, Tetyana О. (Східноєвропейський національний університет імені Лесі Українки, 2017)
Задля порівняльного аналізу громадсько-політичної активності жителів європейських країн застосовано методологічний підхід Європейського соціального дослідження (ЄСД, 2010–2012–2014). Зокрема, аналізуючи політичний складник основного поняття, ми виявили, що висока зацікавленість політикою передбачає більш активну участь у національних виборах, роботу в організаціях політичного та неполітичного спрямування, практику звернень до політичних діячів. Найбільше цікавиться політикою населення країн із високим рівнем життя (Німеччини (21,1 %), Данії (20,5 %), Ізраїлю (16,6 %), Швеції (18,0 %), Швейцарії (16,4 %), Великобританії (16,0 %)). Згідно з Індексами громадсько-політичної активності (О. Боровський), до групи країн-лідерів входять Швеція (0,33), Фінляндія (0,28), Німеччина (0,27), Франція (0,26), Данія (0,24), Норвегія (0,24). Усі держави Східної Європи займають найнижчі сходинки рейтингу. Результати методики верифікують попередні висновки про те, що населення країн із високим рівнем життя є активним учасником політичного життя держави. Жителі тих країн, які більше довіряють парламенту своєї держави, частіше звертаються до представників влади різного рівня (трійка лідерів – Норвегія, Данія, Швеція), і навпаки. Вплив довіри до інституцій на громадсько-політичну активність потребує додаткового вивчення. Participation of the community in political processes is not only an important feature of the society «democraticity», but also a necessary condition for maintaining its stability and development. For the comparative analysis of the socio-political activity of the inhabitants of European countries, the authors used the methodological approach of the European Social Survey (ESS, 2010–2012–2014), taking into account the fact that political ones dominate among the varieties of socio-political activity. In particular, analyzing the political component of the basic concept, it was found that high interest in politics involves more active participation in national elections, work in organizations of political and non-political orientation, and practice of appeals to politicians. Among the countries whose populations are most interested in politics, countries with a high standard of living were Germany (21,1 %), Denmark (20,5 %), Israel (16,6 %), Sweden (18,0 %), Switzerland (16,4 %), Great Britain (16,0 %). According to the indexes of public-political activity (O. Borovsky's methodology), a group of countries with higher rates in comparison with other countries is clearly distinguished. Thus, the group of leading countries includes Sweden (0,33), Finland (0,28), Germany (0,27), France (0,26), Denmark (0,24), Norway (0,24). All countries of Eastern Europe, along with countries such as Estonia, Lithuania and Portugal, rank lowest in the ranking. Thus, the results of the methodology verifies the findings obtained through a one-dimensional analysis of the indicators of the political component of public-political activity of the population, that the population of countries with a high standard of living is an active participant in the political life of the country. There is also the following dependency: residents of those countries that more trust in the parliament of their country, more often turn to authorities of different levels (the three leaders here - Norway, Denmark, Sweden) and vice versa. Given this result, as well as the fact that normative trust as a determinant of relations in society forms an institutional, the influence of the level of trust on the institutions on the level of public-political activity requires statistical confirmation.
Public-Political Activity of the Population of European Countries
Keywords: громадянські практики; зацікавленість політикою; участь у голосуванні на виборах; практика звернення громадян; інституційна довіра; civic practices; interest in politics; electoral participation; citizen’s practice; institutional trust